Impact of Paraquat Herbicide Application on Soil Microbial (Bacterial and Fungal) Populations and Some Physico-Chemical Properties of Soils under Plantain (Musa paradisiaca) Plantation - Ogbemudia, Ikponmwosa; Ifeyinwa, Edosa Valerie; Abraham, Oogboghodo Ikponmwosa; Ejiro, Abamba Esther (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Paraquat, a widely used non-selective herbicide, is commonly applied in plantain (Musa paradisiaca) plantations to suppress weeds. However, its repeated application raises concern about adverse effects on soil microbial communities and key soil properties that determine fertility and sustainability. This study evaluated the impact of paraquat application on soil microbial (bacterial and fungal) populations and some selected physical and chemical properties of soil under a plantain plantation to understand its influence on soil health. Soils were collected from a plantain plantation in Benin City, Nigeria and treated with paraquat at control (0), recommended rate (RR), and twice the recommended rate (2RR). The experiment was laid out in a Completely Randomized Design (CRD) with three replicates per treatment. Microbial populations and soil properties were monitored at 0, 7, and 14 days after application using standard microbiological and physico-chemical analyses. The RR paraquat application stimulated bacterial and fungal populations over time, suggesting microbial tolerance at moderate concentrations. In contrast, the 2RR application suppressed microbial populations, reduced total nitrogen and organic carbon, and altered nutrient dynamics. Available phosphorus and exchangeable cations (K, Ca, Mg, Na) increased with paraquat rate, while exchangeable acidity (H⁺, Al³⁺) decreased. Soil pH and texture influenced paraquat’s bioavailability and effects, with the sandy, moderately acidic soil enhancing its mobility and toxicity at higher doses. Moderate paraquat use can enhance microbial activity and maintain soil fertility, but excessive application disrupts microbial communities and nutrient balance. These findings reveal the need for judicious paraquat application to safeguard soil health and support sustainable weed management.